Antibacterial Activity of Different Extracts of Swietenia Macrophylla King - Azhari, H. Nour; Sandanasamy, Jessinta; M. M., Yusoff (2012)
The study was carried out to screen antimicrobial activity for a new natural,nontoxic and effective antibiotic from plant extract. In this study, Swietenia Macrophylla King was selected and antibacterial activity of extracts from different parts (leaf, fruit cover, seed cover) with various solvents or different fractions of the extracts was studied in laboratory test. The antibacterial activity of these extracts was assessed against two multiple-drug-resistance bacteria strains namely, Escherichia coli and Staphylococcus aureus by the well diffusion method. For the antibacterial bioassay, four concentrations (10, 50, 100 and 150 µg mL-1 ) of each extract solutions were prepared. The antibacterial activity among extracts was extremely broad against both test organisms. Minimum inhibition concentration was done serial dilution method. The MIC values of the extracts ranged from 8.1 to 21.2 µg mL-1 . Among fractionated extracts, fraction 4 (F4) of fruit cover more potent than other fractions, whereas among solvent crude extracts; the ethanol extracts from fruit cover (EFC) displayed overall more potent activity than other parts against both tested bacteria. The experimental results obtained from this study suggest that Swietenia Macrophylla King is promising as natural antibacterial. Some bioactive groups were screened by TLC; and the results obtained were positive and this may warrant further research to determine the bioactive compound(s).